Retained introns in phototransduction genes of 5xFAD mouse retina suggest vision impairment as an early diagnostic marker for Alzheimer’s disease - Hyun-Min Lee; Jinho Kim; Ji-Young Kim; Mi-Jin An; Geun-Seup Shin; Ah-Ra Jo; Yuna Park; Chul-Hong Kim; Yujeong Hwangbo; Ju-Hyun Lee; Tae Kyung Hong; Kun Ho Lee; et al. (Scientific Reports)
Abstract Alzheimer’s disease (AD) is an age-related neurodegenerative disorder characterized by neuronal and synaptic loss in the brain, which leads to cognitive impairment and dementia. Therefore, early diagnosis by employing various biomarkers is crucial for preventing and treating AD. Although retinal pathology is an emerging biomarker associated with AD, detailed molecular mechanisms of retinal impairments remain unclear. Herein, we identified genome-wide dysfunction of alternative splicing in the early stage of 5xFAD transgenic mouse retina by performing RNA sequencing analysis. Notably, retained introns, highly enriched in phototransduction and retinal genes in the 1.5-month-old 5xFAD mouse retina, was significantly associated with physiological impairment of rod photoreceptors in the retina, as evidenced by electroretinogram (ERG) analysis. These results indicate that the abnormal scotopic ERG associated with global splicing impairment may be valuable as an early-detection biomarker for AD.